Contribution Ultra Violet Radiation On Degradation Of Biodegradable Base Oil - Ratu Ulfiati (Scientific Contributions Oil and Gas, 2009)
Increasing environmental awareness led to the development of environmentally harmless lubricants made by biodegradable materials. Biodegradable lubricants are suitable for various kinds of application, one of the promising usages is for railways. Oils or greases are applied for railways or points to keep sufficient friction coefficient or to avoid wear damage. These lubricants are â€œonce-throughâ€ lubricants, and never recovered but defused into the earthâ€™s surface. The oxidation of lubricants on the railways will take place because of the sunlight effect. The solar radiation at the top of earthâ€™s atmosphere contains a significant amount of UV radiation of shorter wavelength, and therefore higher energy. This study shows that the UV-B radiation can deteriorate rapeseed oil immediately. It is showed by the results of peroxide value, total acid number and molecular weight distribution are increased with oxidation time.